1986
DOI: 10.2527/jas1986.63192x
|View full text |Cite
|
Sign up to set email alerts
|

Longissimus Muscle Quality, Palatability and Connective Tissue Histological Characteristics of Bulls and Steers Fed Different Energy Levels and Slaughtered at Four Ages

Abstract: One hundred forty-four Angus male calves were assigned to one of five slaughter-age groups: 9, 12, 15, 18 and 24 mo of age. After weaning, one-half of the calves within slaughter age were castrated. One-half of the 12-, 15-, 18- and 24-mo age groups of each sex were further randomly allotted to a high-energy (HE) or low-energy (LE) finishing diet. Eight bulls and eight steers assigned to the 9-mo slaughter group were fed the HE diet only. Samples from the longissimus muscle (LM) were taken at the 12th rib for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
1
5

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 22 publications
9
29
1
5
Order By: Relevance
“…Schönfeldt and Strydom (2011) also showed that age had no effect on the collagen content of South African cattle. The lack of a diet effect on collagen is in accordance with the results of Dikeman et al (1986).…”
Section: Collagen Content and Solubilitysupporting
confidence: 79%
See 1 more Smart Citation
“…Schönfeldt and Strydom (2011) also showed that age had no effect on the collagen content of South African cattle. The lack of a diet effect on collagen is in accordance with the results of Dikeman et al (1986).…”
Section: Collagen Content and Solubilitysupporting
confidence: 79%
“…Similarly, a lack of any effect of age on the collagen content of the longissimus dorsi (LD) muscle from bulls and steers slaughtered at four ages was reported by Dikeman et al (1986). Schönfeldt and Strydom (2011) also showed that age had no effect on the collagen content of South African cattle.…”
Section: Collagen Content and Solubilitymentioning
confidence: 96%
“…The higher pH of beef from bulls, and the associated darker colour, is consistent with other studies (discussed by Purchas & Aungsupakorn 1993), but the removal of the significant effect of castration on PF-IY when adjustments were made for pH was not expected. The higher values for PF-IY for bulls in the unadjusted data support evidence that the connective tissue of beef from bulls and steers differs slightly in amount or concentration (Boccard et al 1979;Cross et al 1984;Dikeman et al 1986), as there is evidence that Warner-Bratzler initial yield force (IY) is primarily a measure of myofibrillar toughness, whereas the peak force (PF) is a measure of myofibrillar plus connective tissue toughness (Bouton et al 1977;Bouton et al 1981). Therefore the difference (PF-IY) tends to reflect differences in connective tissue toughness.…”
Section: Breed and Castration Effectssupporting
confidence: 63%
“…Similarly, Seideman and Crouse [105] who induced changes in fiber types and diameters by variations in feeding level, did not observe any relationships between fiber characteristics and juiciness. However, Dikeman et al [20] and Keane et al [53] pointed out a positive relationship between juiciness (and tenderness) and muscle fat content. In the latter study, the higher fat content was due to higher carcass weight, and not to an increased feeding level.…”
Section: Juicinessmentioning
confidence: 99%